Architecture Between the Panels: Comics, Cartoons and Graphic Narrative in the (New) Neo Avant‐Garde. (2nd July 2019) - Arana, Luis Miguel Lus
Abstract: Avant‐garde architects from the 1960s onwards drew numerous outside influences into the discipline, reshaping architecture's limits and communicative properties. Architect and researcherLuis Miguel Lus Arana, lecturer in History and Theory of Architecture at the University of Zaragoza in Spain, explores how comic books and cartoons were mobilised by groups such as Archigram, Ant Farm and Utopie to experiment with space and time. This discussion is accompanied by a specially commissioned comic by Lus Arana's alter ego, the cartoonistKlaus, charting this avant‐garde path from the experimental architecture of the mid‐20th century to the protagonists of today.